The Development of Linguistic Thought between Formalism and Mechanization: Grammar and Morphology as a Model - chikhaoui, chouaib; chenene, kouider (El Omda in Linguistics and Discourse Analysis, 2022)
There is a huge development that computer science has contributed to import some characteristics of intelligence to machines (computer), but it is still too early to say that there are programs and models can simulate the ability of the human mind even in its way of thinking, creating and learning. also, as the linguistic lesson has gotten attention from computer scientists, linguists were concern of providing this new science with linguistic basises to be more accurate; Moreover, they did not neglect the application of computing assets to linguistics, especially at the end of the last century until nowadays. however, they benefited from it and study to develop it, just as ancient civilizations transmitted and developed a lot of knowledge from each other.